2011
DOI: 10.1038/emboj.2011.124
|View full text |Cite
|
Sign up to set email alerts
|

Aging and chronic DNA damage response activate a regulatory pathway involving miR-29 and p53

Abstract: Aging is a multifactorial process that affects most of the biological functions of the organism and increases susceptibility to disease and death. Recent studies with animal models of accelerated aging have unveiled some mechanisms that also operate in physiological aging. However, little is known about the role of microRNAs (miRNAs) in this process. To address this question, we have analysed miRNA levels in Zmpste24-deficient mice, a model of Hutchinson-Gilford progeria syndrome. We have found that expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
203
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(216 citation statements)
references
References 59 publications
9
203
0
4
Order By: Relevance
“…The p53 damage response has been shown to decline with age in response to DNA damage in spleen and thymus of mice (Feng et al ., 2007). In other studies, p53 activity was found to be upregulated in noncancerous tissues of aged mice (Edwards et al ., 2007; Ugalde et al ., 2011). We found a less efficient p53 tumor suppressor response, as measured by protein expression, in lung adenomas and hyperplasias from old Kras G12D mice.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 damage response has been shown to decline with age in response to DNA damage in spleen and thymus of mice (Feng et al ., 2007). In other studies, p53 activity was found to be upregulated in noncancerous tissues of aged mice (Edwards et al ., 2007; Ugalde et al ., 2011). We found a less efficient p53 tumor suppressor response, as measured by protein expression, in lung adenomas and hyperplasias from old Kras G12D mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, persistent DNA damage results in Wip1 down-regulation also in MCF-7 cells, which overexpress the phosphatase as a consequence of gene amplification. Repression of Wip1 protein during chronic DDR and in pathological aging has been recently demonstrated in a mouse model of progeria (42). In this model, suppression of Wip1 has been related to miR-29 up-regulation (42).…”
Section: Discussionmentioning
confidence: 99%
“…These data contribute to our understanding of the basic mechanisms regulating osteoclast differentiation and provide insight into the function of miR-29 family members in cells of the hematopoietic lineage and in other tissue types. Dysregulation of miR-29 family members is implicated in the pathology of multiple malignancies and in conditions such as diabetes and fibrosis, and aging (63). Additional studies, in vivo, will better define the role of miR-29 in osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%